2023
DOI: 10.1039/d3cc03104g
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic hydrogen evolution with a copper porphyrin bearing meso-(o-carborane) substituents

Xinyang Peng,
Jinxiu Han,
Xialiang Li
et al.

Abstract: A newly designed copper complex of 5,15-bis(pentafluorophenyl)-10,20-bis(o-carborane)porphyrin (1) was synthesized and tested for electrocatalytic hydrogen evolution reaction (HER). In acetonitrile, 1 was much more efficient than Cu 5,15-bis(pentafluorophenyl)-10,20-diphenylporphyrin (2) for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Cu porphyrins have recently been shown to be highly active and stable for electrocatalytic HER. [42,45,49,50] We showed recently that Cu porphyrins outperformed other transition metal porphyrin analogues for HER under the same conditions. [51] Through controllable β-oxidation using oxone as the oxidant, we made analogue 2 with one β-lactone group as well as analogues 3 and 4 with two β-lactone groups in a cis and trans configuration, respectively.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Cu porphyrins have recently been shown to be highly active and stable for electrocatalytic HER. [42,45,49,50] We showed recently that Cu porphyrins outperformed other transition metal porphyrin analogues for HER under the same conditions. [51] Through controllable β-oxidation using oxone as the oxidant, we made analogue 2 with one β-lactone group as well as analogues 3 and 4 with two β-lactone groups in a cis and trans configuration, respectively.…”
mentioning
confidence: 96%
“…[43][44][45] It is shown that with the introduction of electron-withdrawing substituents, metal porphyrins will become easier to be reduced to generate catalytically active species for proton reduction. [10,38,42] This effect will in general lead to the anodic shift of electrocatalytic HER waves. In addition to the benefits of studying structure-activity relationships, metal porphyrins have very rich and characteristic spectroscopic features, [46][47][48] which are also beneficial for reaction mechanism studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 c They were first loaded onto CNTs to obtain BPD/CNT and BP/CNT using the method reported. 12 The morphologies of BPD/CNT and BP/CNT were then evaluated using scanning electron microscopy (SEM) (Fig. S6, ESI†), which showed no clear aggregation of BPD/CNT and BP/CNT .…”
mentioning
confidence: 99%
“…The high-resolution XPS spectra of Cu 2p 1/2 and Cu 2p 3/2 showed peaks at 935.1 and 955.2 eV, respectively, corresponding to Cu( ii ), which is similar to the XPS result of a hybrid of a porphyrin(1.1.1.1) copper complex and CNTs. 12…”
mentioning
confidence: 99%